Isolation of Temperature-Sensitive Mutants of Murine Sarcoma Virus - Scolnick, Edward M. (1972)
Three separate murine sarcoma virus nonproducer cell lines have been isolated which are temperature sensitive for the maintenance of transformation. In each case, a viral rather than a cellular genetic mutation is the reason for the temperature-sensitive effect. Superinfection of one of the mutants with murine leukemia virus overcomes the temperature-sensitive change in the transformed state.